2010
DOI: 10.1111/j.1364-3703.2009.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamyl alcohol dehydrogenases‐C and D, key enzymes in lignin biosynthesis, play an essential role in disease resistance in Arabidopsis

Abstract: The deposition of lignin during plant-pathogen interactions is thought to play a role in plant defence. However, the function of lignification genes in plant disease resistance is poorly understood. In this article, we provide genetic evidence that the primary genes involved in lignin biosynthesis in Arabidopsis, CAD-C and CAD-D, act as essential components of defence to virulent and avirulent strains of the bacterial pathogen Pseudomonas syringae pv. tomato, possibly through the salicylic acid defence pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
170
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(183 citation statements)
references
References 46 publications
2
170
0
2
Order By: Relevance
“…Several studies have been reported on lignin accumulation in plants under biotic, abiotic stresses [6,29,31]. Based on previous studies it has been known that excess formation of H 2 O 2 will lead to activation of secondary defense responses in plants which will result in the lignification of cell walls, loss of cellular viability and growth [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported on lignin accumulation in plants under biotic, abiotic stresses [6,29,31]. Based on previous studies it has been known that excess formation of H 2 O 2 will lead to activation of secondary defense responses in plants which will result in the lignification of cell walls, loss of cellular viability and growth [16].…”
Section: Discussionmentioning
confidence: 99%
“…Gene duplication in the land plants ancestor of CAD-like genes in Class II and III (such as PtCAD10 and AtCAD6) has been described previously . TgCAD1, a bona fide CAD, was grouped close to AtCAD4 and AtCAD5, and these genes from Arabidopsis participate in pathogen-infected tissues (Tronchet et al 2010). Several genes involved in lignin biosynthesis belong to Class II, such as OsCAD7 (Li et al 2009), AtCAD7 and AtCAD8 (Kim et al 2004) and PtCAD10 (Barakat et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important as the plant cell wall is closely associated with plant defense [115,116]. Genes involving lignin biosynthesis have been found to play important roles in plant defense [117,118]. In Arabidopsis, members of the cinnamyl alcohol dehydrogenases (CAD) gene family, one of the key genes in lignin biosynthesis, were induced by pathogen attack.…”
Section: Taking Feedstocks Through To Field Trialsmentioning
confidence: 99%
“…In Arabidopsis, members of the cinnamyl alcohol dehydrogenases (CAD) gene family, one of the key genes in lignin biosynthesis, were induced by pathogen attack. Moreover, cad mutant lines displayed decreased resistance to pathogens [118]. In addition to differences in pathogen resistance, plants with modified cell walls can also have altered abiotic stress resistance.…”
Section: Taking Feedstocks Through To Field Trialsmentioning
confidence: 99%